การผสานเทคโนโลยีป้องกันกำจัดแมลงศัตรูหน่อไม้ฝรั่งโดยชีววิธี - สุวงศ์ศักดิ์ศรี, สมชัย; สรรพนุเคราะห์, ภัทรพร; พินศรี, นันทนัช; มาลี, สาทิพย์; ศิริพลตั้งมั่น, สมศักดิ์ (Thai Journal of Science and Technology, 2020)
Integrated technology for biological control of insect pests in asparagus was conducted to study the social and economic factors of farmers in Nakhon Pathom and Kanchanaburi provinces during 2016-2018 by using questionnaires. This study aimed to understand the knowledge of biological control of farmers’ attitude in using biocontrol, farmers' crops practice on the use of biological control for controlling pest. Using simple sampling methods with 50 samples, the statistical analysis from the questionnaire found that farmers had a moderate level of understanding of insect pest control on asparagus. Most of them used biological control to prevent insect pest with medium level of understanding. The study was conducted on a farmer’s crop in Nakhon Pathom and Kanchanaburi provinces with a total of 13 plots. The results showed thrips outbreak throughout the production season and found low amount of other pests including whitefly, beet armyworm and leaf-eating caterpillar. By the end of the study, the demonstrative plots showed lower amount of production cost and also lower profits than the actual farmer’s plots. When considering the benefit cost ratio (BCR) of the asparagus production on this project, it was found that the demonstrative plot had a higher benefit of cost ratio than that of the farmer's plot by 3.85 %. The results of opinions and satisfaction survey of farmers who participated in this project, showed that their total satisfaction at the end of the project was overall evaluated at a high level whereas a moderate level of satisfaction was obtained before the training occurred. The farmers wanted to increase an access to bioproducts and the development of bioproducts type should be easy to use and to produce by themselves.